MODERN STATE AND POST-WAR PROSPECTS OF FINANCIAL INCLUSION IN UKRAINE CONSIDERING THE EU EXPERIENCE - Abramova, Iryna; Nedilska, Larysa; Kurovska, Nataliia; Kovalchuk, Oleksandr; Poplavskyi, Pavlo (Fìnansovo-kreditna dìâlʹnìstʹ: problemi teorìì̈ ta praktiki (Online), 2023)
The purpose of the article is theoretical and methodological substantiation of the state and post-war prospects of financial inclusion in Ukraine, taking into account the experience of EU countries. The objectives of the study are as follows: to theoretically substantiate the content and features of financial inclusion, taking into account the experience of EU countries; to assess the current state of financial inclusion; and to outline post-war prospects for the development of financial inclusion in Ukraine. It is argued that the key parameters of financial inclusion are financial well-being, financial behaviour, financial knowledge, and the utilization of financial products, as well as physical access to financial services. Drawing on the experience of EU countries, it is substantiated that creating conditions for free access to financial services for all categories of the population and businesses, as well as their digitalization, contribute to the growth of citizens' income, the simplification of investment mechanisms, and thus the economic development of the country. An assessment of the state of financial inclusion in Ukraine is conducted through online surveys of various categories of citizens. It is determined that Ukrainians feel a strong need for additional sources of income, and the financial situation of the majority of them is extremely unstable. Based on the results of correlation-regression analysis, the priorities of financial inclusion are identified as the level of financial literacy and competency among the population. This will enable them to budget their income and expenses, promote the transformation of savings into investments, and have a positive impact on the post-war recovery of the country's economy.